Nonlinear adaptive sliding mode control with fast non-overshooting responses and chattering avoidance. Issue 7 (May 2017) - González, José Antonio; Barreiro, Antonio; Dormido, Sebastián; Baños, Alfonso
Abstract: It is well known that the main problem hindering the application of the sliding mode control (SMC) is the chattering effect produced by the use of discontinuous switching control functions. In this paper, a combination of several specialized SMC controllers is proposed in order to solve this problem and obtain high accuracy steady state sliding motions in case of a class of MIMO nonlinear systems with external matched disturbances and plant uncertainty. The developed method uses a disturbance estimation, a nominal controller that assumes the cancellation of the disturbance inputs and an error controller that guides the trajectory of the plant states using the nominal response as a tracking reference. The design of the SMC control laws is implemented using an adaptive nonlinear sliding mode definition that creates fast non-overshooting responses over the selected output variables. Numerical simulation results are given to illustrate the effectiveness of the proposed SMC.